In Our Own Image: The Environment and Society as Global Discourse. (1st February 1995) - Redclift, Michael
The environment is clearly shaped by human hands, but it is also shaped by the human mind. The paper examines the way in which the environment is produced, as intellectual capital. It asks about the extent to which the environment can be understood by science and through science. It explores the way in which science, as a cultural form, enables us to construct an environment which is 'manageable', but prevents us from coming to terms with increased uncertainty. Drawing on research about the Canadian frontier in the 1840s and current critiques of environmental economics, the paper concludes by suggesting that research on the global environment should recognise the existence of different, and divergent, understandings of what the global environment is, and how the problems associated with global environmental change can be addressed. This paper is about how the environment is produced. It is about the physical landscape that results from human activities and ingenuity, and the mental landscape that shapes these activities and is shaped by them. It asks whether our environment, any environment, can be understood by science or through science. It explores the way in which our science, as a cultural form, gives rise to our construction of the environment. When I say that the environment is a social construction, what do I mean? Here are some examples: these are the discourses.